2003
DOI: 10.1073/pnas.1131959100
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of short interfering RNA determined through gene expression signatures

Abstract: Short interfering RNA (siRNA) is widely used for studying gene function and holds great promise as a tool for validating drug targets and treating disease. A critical assumption in these applications is that the effect of siRNA on cells is specific, i.e., limited to the specific knockdown of the target gene. In this article, we characterize the specificity of siRNA by applying gene expression profiling. Several siRNAs were designed against different regions of the same target gene for three different targets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
305
6
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(326 citation statements)
references
References 34 publications
6
305
6
6
Order By: Relevance
“…In this respect, some studies have shown that even 11-bp matches between a siRNA and an unintended target is enough to impede that gene [10]. In general, the magnitude of this unwanted activity known as an "off-target effect" was lower than that of the on-target gene, and can be avoided by careful selection of siRNA sequences and working with the lowest effective siRNA concentrations [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, some studies have shown that even 11-bp matches between a siRNA and an unintended target is enough to impede that gene [10]. In general, the magnitude of this unwanted activity known as an "off-target effect" was lower than that of the on-target gene, and can be avoided by careful selection of siRNA sequences and working with the lowest effective siRNA concentrations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some siRNAs have 'off-target' effects, which are often the result of partial homology to other transcripts 11,12 . The shRNA library was designed to avoid off-target effects by minimizing homology of shRNAs to other transcripts (see Methods).…”
mentioning
confidence: 99%
“…For some siRNA, single nucleotide mismatches have been reported to abolish activity, whereas others have reported an absence of RNAi effects only after introduction of 7 mutations (12,13). When, instead of focusing on the target gene alone, all genes are examined for siRNA effects, the picture becomes less clear (14)(15)(16). Three conflicting reports have been published thus far: two describing the absence of any interference of siRNA on non-target mRNA (14,15), whereas the other report claims cross-reaction of siRNA with approximately 0.1% of the investigated 21,000 transcripts with even only limited (seven nucleotides) or no sequence similarity (16).…”
Section: Mechanism Of Rnaimentioning
confidence: 99%
“…When, instead of focusing on the target gene alone, all genes are examined for siRNA effects, the picture becomes less clear (14)(15)(16). Three conflicting reports have been published thus far: two describing the absence of any interference of siRNA on non-target mRNA (14,15), whereas the other report claims cross-reaction of siRNA with approximately 0.1% of the investigated 21,000 transcripts with even only limited (seven nucleotides) or no sequence similarity (16). The differences between these studies could be the result of siRNA concentration as higher concentrations have been associated with a different pharmacological profile (15).…”
Section: Mechanism Of Rnaimentioning
confidence: 99%
See 1 more Smart Citation